ЭКОНОМИЧЕСКАЯ СУЩНОСТЬ И ФОРМИРОВАНИЕ ТАМОЖЕННЫХ ПЛАТЕЖЕЙ (Journal of Economic Research & Business Administration, 2015)
This article discusses the formation and economic essence of import and export duties, as well as the value of the customs value of goods under the Customs Union.